Audit and feedback of antibiotic use - Baysari, M. T.; Oliver, K.; Egan, B.; Li, L.; Richardson, K.; Sandaradura, I.; Westbrook, J. I.; Day, R. O. (Applied Clinical Informatics, 2013)
Background: There is now little doubt that improving antimicrobial use is necessary for the containment of resistance.Objective: To determine whether providing individualised feedback to doctors about their recent compliance with the hospital’s antibiotic policy improves compliance with the policy.Methods: This study was conducted at a teaching hospital in Sydney, Australia. Computerised alerts integrated into the electronic prescribing system (ePS) inform prescribers of the local antibiotic policy. We utilised prescribing data extracted from the ePS for ‘audit and feedback’. Thirty-six prescribers were sent feedback letters via email. We also interviewed doctors who had received letters to explore their views of the feedback and the policy in general.Results: There was no significant change in compliance with the policy following implementation of the feedback intervention (0% compliant vs 11.9%; p = 0.07). Several problems with the policy and the approval process were identified by researchers during auditing and by prescribers during interviews. Some problems identified made it difficult to accurately assess compliance and for doctors to comply with the policy.Conclusions: Our intervention did not result in improved compliance with the antibiotic policy but revealed practical problems with the policy and approval process that had not been identified prior to the trial. Greater support for the policy by senior doctors and the assignment of more clearly defined roles and responsibilities associated with antibiotic use and approval may result in improved compliance. Harnessing the full potential of technology would streamline the antimicrobial approval process and allow more efficient and reliable monitoring of antibiotic use and compliance. Many of the problems we identified are generic issues of importance to all organisations seeking to integrate antimicrobial stewardship into ePS.Citation: Baysari MT, Oliver K, Egan B, Li L, Richardson K, Sandaradura I, Westbrook J I, Day RO. Audit and feedback of antibiotic use: Utilising electronic prescription data. Appl Clin Inf 2013; 4: 583–595http://dx.doi.org/10.4338/ACI-2013-08-RA-0063
Keywords: Antibiotic; compliance; audit and feedback; electronic prescribing